The Challenges in Character Building of Student Santri at SD Negeri Kepohagung Pamotan Rembang - Masaroh, Safi’atullaila; Yani, Ahmad (The Future of Education Journal, 2025)
This research aims to identify challenges in developing the character of students at SD Negeri Kepohagung, Pamotan, Rembang. The character of student students reflects the religious and moral values ​​that are the basis for forming students' personalities in everyday life. This research uses a qualitative approach with descriptive methods. Data was collected through observation, in-depth interviews and documentation studies. The research results show that the main challenges in developing the character of students include a lack of support from the family environment, teachers' lack of understanding of Islamic values, and the increasingly widespread negative influence of social media. Apart from that, limited supporting facilities such as prayer facilities in schools also influence the effectiveness of character development programs. This research recommends increasing collaboration between schools, parents and the community to create a conducive environment for the development of the character of students. In this way, religious values ​​can be internalized more effectively in students' lives.